2015
DOI: 10.1007/s11664-015-3645-4
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Nonohmic Properties of CaCu3Ti4O12/SrTiO3 Ceramics

Abstract: In this work, (1 À x)CaCu 3 Ti 4 O 12 -xSrTiO 3 [(1 À x)CCTO/xST, x = 0% to 2%] ceramic samples were prepared by the solid-state reaction method. The dielectric and electrical properties of CaCu 3 Ti 4 O 12 (CCTO) and CaCu 3 Ti 4 O 12 /SrTiO 3 (CCTO/ST) ceramics were investigated. The results show that a small amount of Sr 2+ can enter the lattice of CCTO. The mean grain size of the ceramic samples increased greatly for x = 0.5% and then decreased for x = 0.75% to 2%. ST addition and Sr 2+ preferential occupan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] This is because many electronic technologies require high-permittivity dielectric material to fabricate small-sized multilayer ceramic capacitors with high energy storage density. Many interesting dielectric and electrical phenomena have been observed in CCTO, in both single-and polycrystalline ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] This is because many electronic technologies require high-permittivity dielectric material to fabricate small-sized multilayer ceramic capacitors with high energy storage density. Many interesting dielectric and electrical phenomena have been observed in CCTO, in both single-and polycrystalline ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the TeO2 doping increases the resistance value of the grain boundaries Rgb and consequently a reduction of the polarization at the low frequency interfaces [21]. Renzhongxue et al synthesized the composite CaCu3Ti4O12-SrTiO2 (x=0.0 at 0.02) using the solidstate route and revealed that the addition of SrTiO3 causes increase in the dielectric constant and a decrease and a decrease in the loss tangent this leads to an improvement in the linear current-voltage properties have been considerably enhanced [22]. Inthiswork, we synthesis a new((1-x) CCTO-x PL0.2T (x=0.0; 0.2; 0.3; 0.4; 0.7 and 1.0) compositesbyhybrid method.…”
Section: Introductionmentioning
confidence: 99%